PRESCRIPTION PATTERN OF DIURETICS IN A TERTIARY CARE HOSPITAL - Chithara, P G; R, Dr. Yogananda; DR, Dr. Bharathi (Journal of Biomedical and Pharmaceutical Research, 2019)
Diuretics are drugs that increase the rate of urine flow; clinically useful diuretics also increase the rate of excretion of Na+ (natriuresis) and an accompanying anion, usually Cl. Diuretics are a mainstay of therapy for a wide variety of diseases ranging from hypertension to the nephrotic syndrome. Objective: To study the prescribing patterns of diuretics in General Medicine and ICU. To assess the drug-drug interaction of diuretics. To study the route of administration of diureics. Materials and methods: A prospective observational study was conducted over a period of six months at general medicine and ICU department of Basaveshwara Medical College and Hospital and Research Centre, Chitradurga.a otal of 100 in-patients are included as study subject. Results: Mostly prescribed diuretic in this study were furosemide (52.9%), followed by mannitol (28.1%), spironolactone (11.57%), torsemide (5.79%), amiloride (0.82%) and hydrochlorothiazide (0.82%). Out of 100 prescriptions 84.4% of diuretics prescribed in intravenous route, 15.6% of diuretics prescribed in oral route. Out of 100 prescriptions total 89 drug interactions with diuretics are found. In that 2.3% major interactions and 67.4% moderate interactions and 30.3% minor interactions are found. Conclusion: Prescription monitoring helped to reduce the diuretic usage errors with respect to dose and drug-drug interaction with other prescribed drugs to provide better patient care. Keywords: prescribing pattern, drug-drug intraction, diuretics